2020
DOI: 10.1016/j.adro.2020.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Stereotactic Radiation Therapy With a Jawless Ring Gantry Linear Accelerator Equipped With New Dual Layer Multileaf Collimator

Abstract: To test the feasibility of a simplified, robust, workflow for intracranial stereotactic radiation therapy (SRT) using a ring gantry linear accelerator (RGLA) equipped with a dual-layer stacked, staggered, and interdigitating multileaf collimator. Materials and Methods: Twenty recent clinical SRT cases treated using a radiosurgery c-arm linear accelerator were anonymized. From these data sets, a new planning workflow was developed and used to replan these cases, which then were compared to their clinical counte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 34 publications
3
21
0
Order By: Relevance
“…All parameters were deemed acceptable for treating prostate SBRT patients on Halcyon with overall faster treatment time of less than 10 minutes, potentially benefiting patients who cannot lie flat in the treatment position for longer treatment time, minimizing intrafraction motion error and improving clinic efficiency. Based on this research and other previous studies, we are planning to expand our Halcyon Linac to treat other disease sites such as fractionated stereotactic treatment of brain tumors 36,37 any abdominal and pelvic nodes SBRT and selected liver, pancreas or adrenal glands SBRT patients. Due to lower total MU per treatment and relatively smaller beam‐on time, deep inspiration breath‐hold to liver or pancreatic SBRT treatments on Halcyon Linac warrant future investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All parameters were deemed acceptable for treating prostate SBRT patients on Halcyon with overall faster treatment time of less than 10 minutes, potentially benefiting patients who cannot lie flat in the treatment position for longer treatment time, minimizing intrafraction motion error and improving clinic efficiency. Based on this research and other previous studies, we are planning to expand our Halcyon Linac to treat other disease sites such as fractionated stereotactic treatment of brain tumors 36,37 any abdominal and pelvic nodes SBRT and selected liver, pancreas or adrenal glands SBRT patients. Due to lower total MU per treatment and relatively smaller beam‐on time, deep inspiration breath‐hold to liver or pancreatic SBRT treatments on Halcyon Linac warrant future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In a hypofractionated study, Knutson et al. reported a retrospective dosimetric analysis of intracranial stereotactic radiation therapy (SRT) treatments using the Halcyon Linac 36 . In a 20‐patient study with a fractionation scheme of 30 Gy in five fractions, they demonstrated that acceptable plan quality for brain SRT is achievable using Halcyon coplanar geometry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26] For hypofractionation schemes, Knutson et al reported a retrospective dosimetric study of fractionated intracranial stereotactic radiation therapy (SRT) using the Halcyon. 27 In a 20-patient study (30 Gy in five fractions), they demonstrated acceptable plan quality for brain SRT using Halcyon coplanar geometry. Another study by Li et al demonstrated the Halcyon V2.0 can generate plan quality comparable to a C-arm Linac for 6-10 brain tumors (diameter >1.0 cm), with a single-isocenter VMAT approach for intracranial radiosurgery.…”
mentioning
confidence: 94%
“…For hypofractionation schemes, Knutson et al. reported a retrospective dosimetric study of fractionated intracranial stereotactic radiation therapy (SRT) using the Halcyon 27 . In a 20‐patient study (30 Gy in five fractions), they demonstrated acceptable plan quality for brain SRT using Halcyon coplanar geometry.…”
Section: Introductionmentioning
confidence: 99%